INTEGRATION OF DESIGN APPROACHES AND VARIATIVE METHODS IN THE EDUCATIONAL PROCESS - Husniddin Tojiev (The Conference Hub, 2025)
This article examines the importance of integrating design approaches and variational methods in the educational process. Project-based learning allows students to think creatively, develop practical skills, and learn independently. Variational methods, on the other hand, help to adapt the educational process to individual needs, increase students' analytical thinking and creativity. The article shows the possibilities of creating qualitative changes in education through the integration of these two approaches.
Keywords: education, variability, methodology, effectiveness, educational process, innovative methods, pedagogical views.